Prevalence and resistance profile to antibiotics of diabetic foot infections isolated microorganisms - Bocanegra-García, Virgilio (Universidad Autónoma de Tamaulipas, 2014)
Diabetes mellitus (DM) is a chronic disease that affects a considerable portion of the population and type 2 diabetes represents a serious current public health problem in Mexico. Diabetic foot is a severe consequence of diabetes for its prevalence, the frequency of resulting infections, and the high social and economic costs. In this study we examined 382 isolated families of infections in 284 patients to determine their identity by biochemical tests and their drug resistance profile. Of the 382 isolates, 186 samples (48.6 %) were positive Gram bacteria; 182 samples (47.6 %) were negative Gram bacteria; and 14 (3.6 %) were Candida sp. In 158 of the 284 samples (55.6.%) only one type of bacteria was identified; in 113 samples (39.7 %) a mixed culture was found, with 7 samples containing both bacteria and yeast and 13 samples resulting negative. The most prevalent pathogens were Staphylococcus aureus and Pseudomonas aeruginosa. In S. aureus isolates, 63.9 % was resistant to MRSA; 4.1 % was resistant to vancomicyn; and 18.6 % was resistant to imepenem. P. aeruginosa was the most prevalent Gram negative isolated and also the one with the most drug resistance. Drug-resistance analysis showed that the majority of S. aureus were MRSA and in P. aeruginosa, families resistant to all tested antimicrobials prevailed.